Prevalencia de varias entidades patológicas en bovinos del Magdalena Medio. - Hurtado A, Gabriel; Orrego Uribe, Alberto; Castellanos, Dolly de (Instituto Colombiano Agropecuario - ICA, 2018)
Ganadería bovina